Sharing Knowledge, Technical Skills, and Entrepreneurial Motivation to Improve IKM Performance during the Covid-19 Pandemic: Berbagi Pengetahuan, Keterampilan Teknis, dan Motivasi Wirausaha dalam Meningkatkan Kinerja IKM dimasa Pandemi Covid-19 - Ardiawan Rizaldy; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study aimed to investigate the impact of Knowledge Sharing, Technical Skills, and Entrepreneurial Motivation on the performance of micro, small, and medium enterprises (IKM) involved in the production of fermented soybean cake and tofu in the villages of Kedung Boto, Taman, Sidoarjo, amidst the challenging circumstances of the COVID-19 pandemic. A non-probability sampling method with a saturated sampling approach was employed, resulting in a sample size of 40 respondents. Multiple linear regression analysis, using SPSS version 22, was conducted to analyze the data. The findings revealed that Knowledge Sharing, Technical Skills, and Entrepreneurial Motivation each had a significant partial effect on IKM Performance (p < 0.05). These results imply that fostering knowledge exchange, enhancing technical competencies, and cultivating entrepreneurial drive can significantly contribute to the performance of IKMs in the face of adverse conditions such as the ongoing pandemic. Such insights are invaluable for policymakers, business owners, and stakeholders seeking to empower IKMs and promote their resilience and sustainability in challenging times. Highlights: The study explores the influence of Knowledge Sharing, Technical Skills, and Entrepreneurial Motivation on the performance of IKMs during the COVID-19 pandemic. The research adopts a quantitative approach, utilizing multiple linear regression analysis to examine the relationships between the variables. Findings indicate that Knowledge Sharing, Technical Skills, and Entrepreneurial Motivation significantly impact the performance of IKMs, emphasizing the importance of these factors in enhancing IKM resilience and sustainability in challenging times. Keywords: Knowledge Sharing, Technical Skills, Entrepreneurial Motivation, IKM Performance, COVID-19 Pandemic.